MASS SPECTROMETRIC ANALYSIS FOR THE IDENTIFICATION OF THUNNUS GENUS FOUR SPECIES - T. Pepe; M. Ceruso; A. Carpentieri; I. Ventrone; A. Amoresano; A. Anastasio (Italian Journal of Food Safety, 2011)
An accurate identification of similar fish species is necessary to prevent illegal substitution and is imposed by labeling regulations in UE countries (1). The genus Thunnus comprises many species of different quality and commercial value. The increasing trade of fish preparations of the species included in this genus and the consequent loss of the external anatomical and morphological features enables fraudulent substitutions. This study reports data relating to the proteomic analysis of four tuna species (T. thynnus, T. alalunga, T. albacares, T. obesus). Sarcoplasmic proteins were studied by mono and two dimensional electrophoresis. The most significant proteins for the characterization of the species were analyzed by mass spectrometric techniques. As reported in a previous study (2), an accurate identification of the species seems possible, owing to the polymorphism displayed by the species of the Thunnus genus.